Role of Ovarectomy and D-Galactose Load to Cognitive Function and Behavior of Sprague Dawley - Rosalina, Linda; Mariati, Nelly; Judijanto, Loso; Aliyah, Siti Hamidatul; Lestary, Tanti Tri; Asman, Aulia (South Eastern European Journal of Public Health, 2024)
The interplay between hormonal imbalance and oxidative stress plays a critical role in age-related cognitive decline. This study investigates the effects of ovariectomy (OVX) and D-galactose (D-Gal) administration on cognitive function and behavior in Sprague Dawley rats. Ovariectomy is commonly used to model post-menopausal conditions in animals, while chronic D-Gal exposure induces oxidative stress, mimicking aging.In this experiment, female Sprague Dawley rats were divided into four groups: a control group, an OVX group, a D-Gal group, and an OVX+D-Gal group. Cognitive performance was assessed using maze tests, while behavioral changes were evaluated through activity and anxiety-related behavior assays. Biochemical analyses were performed to measure oxidative stress markers in the brain tissue.The results indicated significant cognitive impairment and behavioral changes in the OVX and D-Gal groups, with the OVX+D-Gal group showing the most pronounced deficits. Oxidative stress levels were elevated in the OVX+D-Gal group, suggesting that the combination of hormonal deficiency and oxidative stress accelerates cognitive decline. These findings highlight the importance of addressing both endocrine and oxidative stress pathways in the prevention of age-related cognitive dysfunction.This study provides valuable insights into the mechanisms underlying neurodegenerative processes and suggests potential therapeutic targets for cognitive decline associated with aging and menopause.